Promotion Strategies in Increasing the Interest of New Prospective Students in Educational Institutions: Strategi Promosi dalam Meningkatkan Minat Calon Peserta Didik Baru di Lembaga Pendidikan - Hartati, Diah Vitaloka; Nurmala, Eka; Siregar, Muhammad Sapril; Malau, April Gunawan; Saifudin, Iksan (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2025)
The era of globalization and rapidly developing information technology, educational institutions face increasingly complex challenges in attracting the interest of prospective new students. Marketing in education has grown rapidly along with the increasing need for quality educational services. The method used in this study is the Systematic Literature Review (SLR), which aims to identify, evaluate, and interpret all research relevant to a particular research question, topic area, or phenomenon of concern. The results of this study are: 1) Promotional strategies play a crucial role in increasing the interest of prospective new students in educational institutions, the implementation of appropriate strategies, such as digital marketing, promotional mix, public relations, improving the quality of services and facilities, as well as scholarship and discount programs, can significantly increase the attractiveness of educational institutions; and 2) Educational institutions need to continue to adapt to technological developments and market dynamics to design effective promotional strategies that are in accordance with the needs and preferences of prospective students.